FAKTOR – FAKTOR PENYEBAB RENDAHNYA AKSEPTOR ALAT KONTRASEPSI DALAM RAHIM DI BPM SUCI PAIMIN KECAMATAN BENDOSARI KABUPATEN SUKOHARJO - Endrat Kartiko Utomo; Wahyu Hidayati; Mursudarinah (Universitas Duta Bangsa Surakarta, 2021)
Introduction: The rationale for the birth of family planning in Indonesia is the population problem. The important aspects of population are the size of the population, the number of population growth, the number of deaths, and the number of population movements. Based on data from the Central Java Province BKKBN, the number of IUD KB participants in 2014 was 472,217. Objective: to describe the factors causing the low acceptors of intrauterine devices at BPM Suci Paimin, Bendosari District, Sukoharjo Regency. Method: This research method uses a single variable with a non-probability sampling technique, namely accidental sampling. Family planning acceptors at BPM Suci Paimin, Toriyo Village, Bendosari District, Sukoharjo Regency, were 57 respondents. The measuring instrument used is a questionnaire. Results: This study found that the factors that caused the low acceptors of intrauterine devices were elementary education at 42.1%, environmental factors did not support it at 86.0%, and husband's support 100% husband did not support or approve. Conclusion: The factors causing the low acceptors of intrauterine devices, the factor at BPM Suci Paimin, Bendosari District, Sukoharjo Regency, is the husband's most dominant support factor because 100% of husbands do not support or approve.